Geological-geophysical study for the disign of a hazardous waste landfill in Albania - Beqiraj, A.; Alikaj, P.; Lamaj, M.; Muceku, Y.; Çanga, B.; Leka, G. (Bulletin of the Geological Society of Greece, 2007)
Industrial wastes in Albania belong to four main groups: i) wastes from the industrial hot spots, ii) wastes from the old chemical storages, Hi) wastes from mining and ore processing and iiii) wastes from present and future industries. The landfill for hazardous waste is intended as a facility to enable the clean-up of old mostly abandoned industrial sites (the hot spots and other sites), storages of obsolete chemicals and treat and dispose of hazardous waste presently generated in Albanian industry. The technical design of the landfill was anticipated by complex geological study including the geological, geophysical, geotechnical and hydrogeological surveys. All the above surveys aimed to find the best clay terrains with suitable geotechnical and hydrogeological features for the landfill design